2003
DOI: 10.1007/s00122-003-1198-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of genomic regions underlying barley yellow dwarf tolerance in cultivated oat (Avena sativa L.)

Abstract: Barley yellow dwarf (BYD) is one of the most important viral diseases in small grains, including oat (Avena sativa L.). Breeding for BYD tolerance is an effective and efficient means to control the disease. Characterization of major sources of tolerance, and identification of marker and the trait associations, will directly benefit breeding for BYD tolerance. Genomic regions underlying BYD tolerance were mapped and characterized in an oat population consisting of 152 recombinant inbred lines from the cross of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…A broad and continuous distribution was observed for BYDV tolerance across the panel and is in agreement with previous work that shows host plant tolerance for BYDV is multigenic [ 24 – 26 , 46 ]. High heritabilities were observed which is consistent with recently observed heritability [ 27 ] but is higher than historical observations [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A broad and continuous distribution was observed for BYDV tolerance across the panel and is in agreement with previous work that shows host plant tolerance for BYDV is multigenic [ 24 – 26 , 46 ]. High heritabilities were observed which is consistent with recently observed heritability [ 27 ] but is higher than historical observations [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is believed that two to four genes are responsible for BYDV tolerance in oats [ 24 ]. Four QTL (BYDq1, BYDq2, BYDq3 and BYDq4) for BYD tolerance were identified [ 25 ] and were found on linkage groups OM1, 5, 7 and 24. Several other chromosomal regions with BYDV tolerance QTL have been identified in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Jin et al (1998) and Barbosa-Neto et al (2000) respectively identified a further 20 and 5 chromosomal regions with linkage to BYD tolerance, and additional loci were identified by Zhu et al (2003) . Inability of the present study to map more than one locus and detection under only one environment may be related to the natural BYD infection used in phenotyping.…”
Section: Discussionmentioning
confidence: 98%
“…Because this is against the common concept of tolerance used by both pathologists and evolutionary biologists, we will not further discuss these works. QTLs for tolerance have been identified in several plant-pathogen interactions (e.g., [ 87 , 88 , 89 , 102 , 103 ]). Interestingly, a common conclusion of these works is that a few genes determine tolerance, although their functions have not been characterized.…”
Section: Mechanistic Basis and Genetic Determinants Of Plant Tolermentioning
confidence: 99%